Inhibition of growth and expression of inflammation mediators in human leukemic cell line U-937 by a nutrient mixture - Roomi, M.W.; Kalinovsky, T.; Roomi, N.W.; Rath, M.; Niedzwiecki, A. (Experimental Oncology, 2013)
Aim: A nutrient mixture (NM) containing ascorbic acid, lysine, proline and green tea extract has exhibited anticancer activity in vitro and in vivo in a number of cancer cell lines. We investigated the effect of NM on human leukemic myeloid U-937 cells in vitro by measuring: cell proliferation, MMP expression, invasion, apoptosis, and COX-2 and COX-1 protein expression. Methods: Human leukemic cell line U-937 (ATCC) was cultured in RPMI medium supplemented with fetal bovine serum and antibiotics. After 24 h, the cells were treated with NM at 0, 50, 100, 250, 500 and 1000 Ојg/ml, in triplicate at each dose. Phorbol 12-myristate 13-acetate (PMA), 100 ng/ml was added to cells to induce MMP-9 secretion. Cell proliferation was evaluated by MTT assay, MMP expression by gelatinase zymography, invasion through Matrigel, apoptosis by using live green caspase detection kit (Molecular Probe), and COX-2 and COX-1 expression by Western blot. Results: NM had no effect on U-937 cell growth at a concentration of 250 Ојg/ml and exhibited an antiproliferative effect at 500 Ојg/ml concentration. Zymography did not demonstrate MMP-2 or MMP-9 secretion in normal cells; however, PMA strongly induced MMP-9, which was inhibited by NM in a dose-dependent manner. Cell penetration through Matrigel was significantly reduced (by 95%) at 250 Ојg/ml NM and completely blocked at 500 Ојg/ml NM. NM induced slight apoptosis at 100 Ојg/ml and moderate at 500 and 1000 Ојg/ml concentration. NM inhibited COX-2 expression in a dose-dependent fashion and had no effect on COX-1 expression. Conclusions: Our results suggest that NM has potent inhibitory effects on U-937 cell growth and expression of inflammatory mediators, significant parameters in AML progression.